The Use of Azhari Curriculum in Arabic Language Learning at Islamic Boarding School - Eka Fitria Fidayani; Farikh Marzuki Ammar (Nazhruna: Jurnal Pendidikan Islam, 2023)
eLKISI Islamic Boarding School adapts the curriculum from Al-Azhar Cairo or what is called the Az-Azhar curriculum. The Al-Azhar curriculum is a foreign curriculum adapted in Indonesia through the Cakrawala Insan Azhari Foundation as an institution that bridges the eLKISI Islamic Center Islamic Boarding School in implementing this curriculum. The purpose of this study is to know and understand the preparation for learning Arabic with the Al-Azhar curriculum at the Islamic Center eLKISI Islamic Boarding School; in order to know and understand the implementation of learning Arabic with the Al-Azhar curriculum at the eLKISI Islamic Boarding School; as well as to know and understand the learning evaluation process with the Al-Azhar curriculum at the Islamic Center Islamic Boarding School eLKISI. This study uses a qualitative method. The research was conducted by means of interviews, observation and then analyzing the data. The results of the analysis will be carried out by reducing data, presenting data and drawing conclusions. From the data presented, the research entitled "Using the Azhari Curriculum in Arabic Language Learning at the Islamic Center eLKISI Islamic Boarding School" will discuss teacher preparation in preparing for Arabic learning by providing training to Arabic teachers and also guest lectures brought in from abroad. and professors of Arabic, in order to implement it for students so that it is easy to receive and understand lessons and can speak Arabic fluently. Then it will be evaluated by the teachers, in order to create better learning and results in the future.